Strongly Cancellation Modules - A. Elewi , Alaa (Iraqi Journal of Science, 2023)
Let M be an R-module. We introduce in this paper the concept of strongly cancellation module as a generalization of cancellation modules. We give some characterizations about this concept, and some basic properties. We study the direct sum and the localization of this kind of modules. Also we prove that every module over a PID is strongly module and we prove every locally strong module is strongly module.